Prokaryotic community (mayor clades contributing >0.1% of the total 16S rRNA sequences) in an oxygen-deficient upwelling system during La Niña (2018) and El Niño (2019) - Silvia Pajares; Martin Merino; Laura Farías (PANGAEA, 2023)
Seawater samples were collected with 10-L Niskin bottles in four stations along a cross-shore transect in front of the Port of Mazatlán (Mexico) during the oceanographic cruises Maz IV (April 2018) and Maz V (April 2019) on board the R/V “El Puma” (UNAM). Samples for molecular analyses (16S rRNA sequences) were collected at different depths based on the oxygen and chlorophyll-a profiles: surface (5 m depth); deep chlorophyll maximum (at 10–45 m depth, except in the coastal station S1 of Maz V where a sample was collected at the mixed layer); base of the oxycline (at 60–125 m depth); OMZ core (only for Maz IV at 250 m depth); and bottom (between 23 m depth in S1 and 670 m depth in S4). Water samples were filtered on board through polycarbonate membranes (0.22-μm pore, Merck Millipore). Genomic DNA was extracted with the DNeasy PowerWater Kit (Qiagen). The V3–V4 region of the 16S rRNA gene was amplified using the index and adaptor-linked primers Bakt_341F and Bakt_805R, and then sequenced using a 2 exttimes 300 bp paired-end Illumina Miseq system. Amplicon libraries were analyzed with the software QIIME 2.